Refleksi konseptual misi Yesus melalui keramahan gereja di Indonesia - Simanjuntak, Fredy; Papay, Alexander Djuang; Lahagu, Ardianto; Evimalinda, Rita; Ferry, Yusak Hentrias (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
Jesus, reflecting on the context of the mission in the Gospels, often touches on various dimensions, both physical, emotional, intellectual, social, and spiritual for each person and his environment. Many Gospel narratives show the face of friendliness as well as the social responsibility of Jesus in public spaces. Jesus didn't just stop at the gracious nature of God in His mission of ministry but also inspired his listeners to bring out the same kind of hospitality that Jesus did. This needs to reflect the portrait of church life in Indonesian society, which in general tends to focus on religious formalism. This paper aims to explore the concept of Jesus' mission and to realize it practically in the context of Indonesian society today. The method used is descriptive analysis and a hermeneutic approach to the narratives in the Gospels. This study seeks to offer a contextual concept and model of Jesus' ministry to the community served not only as an object of God's hospitality but also as a subject who actively participates in presenting hospitality in public spaces. In conclusion, the mission that Jesus intended to be carried forward by the church was God's mission which Jesus himself had accomplished during his earthly ministry, namely manifesting God's hospitality for humans through the preaching of the gospel and social care.AbstrakYesus, dalam konteks misi di Injil, kerap menyentuh berbagai dimensi, baik secara fisik, emosi, intelektual, sosial, dan spiritual, setiap orang dengan lingkungannya. Narasi Injil banyak menunjukkan wajah keramahan sekaligus tanggung jawab sosial Yesus di ruang publik. Yesus tidak hanya berhenti pada sifat keramahan Allah dalam misi pelayanan-Nya, namun juga menginspirasi para pendengarnya untuk menghadirkan keramahan yang sama, seperti yang Yesus lakukan. Hal ini perlu menjadi refleksi potret kehidupan bergereja pada masyarakat Indonesia, yang umumnya cenderung terfokus kepada formalisme agawami. Artikel ini bertujuan untuk menggali konsep misi Yesus serta merealisasikan secara praktis dalam konteks masyarakat Indonesia di masa ini. Metode yang digunakan adalah analisis deskriptif serta pendekatan yang hermeneutis pada narasi kitab-kitab Injil. Penelitian ini berupaya menawarkan konsep dan model pelayanan Yesus yang kontekstual kepada komunitas yang dilayani, bukan hanya sebagai objek keramahan Allah, namun sekaligus sebagai subjek yang aktif berpartisipasi menghadirkan keramahan pada ruang publik. Kesimpulannya, jelas terlihat bahwa misi yang dimaksudkan Yesus untuk diteruskan oleh gereja adalah misi Allah yang telah dikerjakan Yesus sendiri selama pelayanan-Nya di dunia, yaitu memanifestasikan keramahan Allah bagi manusia melalui pemberitaan Injil dan kepedulian sosial.